An alternative approach to estimating supply response of a perennial crop - Habibah Suleiman (2019)
In previous studies on natural rubber supply, lags have often been incorporated in economic and econometric models designed to explain the dynamic supply response. These lags in input and output prices have not, however, reflected directly the restrictions involved in the growth process for rubber trees. Often these lag structures have been superimposed on models based on static economic theory rather than being based on dynamic economic theory. The phenology for tree crops plays a valuable role in the determination of output levels and supply response. In this paper, the foundation of the supply response specification for rubber is the theory of adjustment cost where the production function incorporates the investment rather than the price expectation model. This was reflected in the results obtained from the impact multiplier and sensitivity analysis. The incorporation of prior information or the phenological process together with economic structure improves the dynamic property of the model.